2011
DOI: 10.1007/s10484-011-9149-y
|View full text |Cite
|
Sign up to set email alerts
|

moBeat: Using Interactive Music to Guide and Motivate Users During Aerobic Exercising

Abstract: An increasing number of people are having trouble staying fit and maintaining a healthy bodyweight because of lack of physical activity. Getting people to exercise is crucial. However, many struggle with developing healthy exercising habits, due to hurdles like having to leave the house and the boring character of endurance exercising. In this paper, we report on a design project that explores the use of audio to motivate and provide feedback and guidance during exercising in a home environment. We developed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 9 publications
0
32
1
2
Order By: Relevance
“…The potential scope of auditory-motor synchronization as a performance enhancement tool has been demonstrated by the recent development of products that help attune musical content to the actual or desired work rate during running, cycling, rowing, and circuit-class training (e.g., [14], [15], [16], [17]) as well as by recent scientific findings in the context of sports or exercises (i.e., [18], [19], [20], [21]). Specifically, Simpson and Karageorghis demonstrated superior performance (i.e., faster times) of 400 m sprints completed in a synchronous music condition in comparison to a no-music control condition [20].…”
Section: Introductionmentioning
confidence: 99%
“…The potential scope of auditory-motor synchronization as a performance enhancement tool has been demonstrated by the recent development of products that help attune musical content to the actual or desired work rate during running, cycling, rowing, and circuit-class training (e.g., [14], [15], [16], [17]) as well as by recent scientific findings in the context of sports or exercises (i.e., [18], [19], [20], [21]). Specifically, Simpson and Karageorghis demonstrated superior performance (i.e., faster times) of 400 m sprints completed in a synchronous music condition in comparison to a no-music control condition [20].…”
Section: Introductionmentioning
confidence: 99%
“…It probably has an activating effect on the immune system, as evidenced by measuring Salivary Immunoglobulin A (SlgA) during instrument playing or singing, in comparison to passive music listening ( Kuhn, 2002 ; Kreutz et al, 2004 ), and an increase of cortisol levels during choir singing. Furthermore, it could be shown that music can increase perceived movement motivation and experienced mood ( van der Vlist et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conforme pasan los años, para las personas resulta más tedioso realizar actividad física debido a la falta de motivación intrínseca y extrínseca, por consiguiente, tener un peso corporal saludable es bastante complicado (van der Vlist, Bartneck & Mäueler, 2011). Muchas personas ven el realizar ejercicio aeróbico como un trabajo aburrido y desagradable, por lo tanto, para poder practicar dicha actividad es necesario mantener constantemente una motivación intrínseca.…”
unclassified